Harnessing Arduino-Based Labs for Monitoring and Optimizing Biological Processes - Kuchkorov Akhlidin Mirzokhid ugli; Yoqubov Abutolib Ahmadali ugli (Research Parks Publishing LLC, 2023)
The utilization of Arduino-based laboratories has emerged as a valuable tool for monitoring and controlling environmental factors in biological processes. This article presents a comprehensive methodology for setting up an Arduino-based laboratory to monitor temperature, pH, and oxygen levels. The methodology includes sensor selection, calibration techniques, power supply considerations, data acquisition and storage methods, environmental factor management, user interface design, and safety considerations. By following these methods, researchers and educators can collect real-time data, analyze trends, and gain valuable insights into various biological phenomena. The successful implementation of the Arduino-based laboratory enables advancements in biotechnology research and education, optimizing biological processes and enhancing our understanding of complex biological systems.